S Sistem Pakar Mendiagnosa Kerusakan Smartphone Android Menggunakan Metode Certainty Factor: Sistem Pakar Mendiagnosa Kerusakan Smartphone Android Menggunakan Metode Certainty Factor - Fitriyani, Mia; Rohayani, Hetty; Santoso, Heri (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
Technological developments such as smartphones are internet enabled telephones which provide many functions and benefits for the wider community, not only for SMS and telephone calls but users can freely do their work, because smartphones are easy to carry everywhere and are also practical compared to laptops. and however, only a few people who use smartphones are sensitive to smartphone damage problems, such as damage to the smartphone hardware in the IC Power system, Display/Touch Screen, damaged battery, damage to the LCD, speakers, etc. so that Most people are unaware and don't care about the symptoms of damage until the smartphone is actually damaged. To be able to provide information about how to detect the type of damage by using the Excel application to find out the symptoms of damage by using the code and uncertainty factor formula. If the result is positive with a high percentage then it can be said to be certain and if the result is negative with a low percentage then it can be said not sure Someone who is not an expert or expert uses an expert system to improve problem solving abilities, while an expert uses an expert system for knowledge assistants. There are two important parts in an expert system, namely the development environment and the consulting environment